(untitled) (International Journal of Built Environment and Sustainability, 2019)
This paper aims to determine the performance of the air well system in a hot and humid tropical climate with existing full-scale air well of single-storey terraced house. The application of air well in residential building widely applied in a traditional building, especially in the Middle East and Europe countries. However, resulted from the development, the application of passive cooling strategies such as air well is gradually replaced by a mechanical cooling system. The aim of the study is to investigate the cooling system role in tropics, where hot and humid climate the overheating of building interior are a critical dilemma due to solar penetration through building fenestration. A field measurement has been carried out in a single storey terraced house with built-in air well in Kuching, Sarawak for 5 days. The field measurement investigates the thermal performance of the single-storey terrace house air well under tropical context. The investigation was measured with U-12 HOBO data logger for temperature and humidity while the air velocity was measured with HD32.3 DeltaOhm measurement logger. Both types of the instrument placed in the air well in a vertical position while another U12 HOBO datalogger placed in a test room with window connected to air well. The outdoor weather data set were measured with HOBO U30. Findings show that the under Malaysia tropical climate, the mean air velocity induced by the air well throughout the measurement days marked as 0.91m/s while during the hottest hour of the measurement days, the air velocity induced in the upper air well could reach 1.09m/s with an outdoor air temperature of 33.6°C and solar radiation of 198 Wh/m². The findings of the study have explained the effectiveness of the air well in providing the thermal performance in the indoor environment and further study on modification of the air well configuration could enhance the airflow and air temperature